Pelatihan Pembuatan Media Pembelajaran IPA berbasis Simulasi PhET dengan Model Discovery Learning terhadap Guru-Guru Sekolah Menengah Pertama di Desa Poowo Kecamatan Kabila Kabupaten Bone Bolango - Ritin Uloli; Trisnawaty Junus Buhungo; Supartin Supartin (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2024)
The role of learning media based on virtual lab simulations that can improve student learning outcomes in understanding the concept of physics in hydrostatic pressure material is by using the PhET (Physics Education Technology) simulation application. This virtual lab media or simulation contains simulations in learning physics, biology, chemistry, etc. PhET simulation was developed in order to assist students in understanding abstract concepts in lessons.